21st-Century Skills of Social Studies Students: Basis for a Proposed Training Program - V. Rogayan Jr, Danilo; Gallardo, Carlisle B.; T. Lacaste, Jerrica; Joyce A. Roque, Darley (Future Science / FSH-PH Publications, 2021)
Enhancing the 21st-century skills of learners will significantly help them become future-ready and globally-competent workforce in the global economy in the context of the fourth industrial revolution. This descriptive cross-sectional survey determined the 21st-century skills of junior high school learners as an input for a suggested training program. A total of 120 seventh grade learners of a public secondary school in Central Luzon, Philippines responded to the 21st-Century Skills Questionnaire (α=0.960). Results showed that the respondents have a moderate level of attainment of the 21st-century skills (M=3.46, SD=0.66). They moderately exhibit learning and innovation skills (LIS) (M= 3.32, SD=0.66), and highly exhibit information, media, and technology skills (IMTS) (M=3.53, SD=0.82), and life and career skills (LCS) (M=3.53, SD=0.74). Female students have higher overall 21st-century skills, and LIS than their male counterparts based on the independent sample t-test result. Furthermore, there is a significant correlation between LIS and IMTS (r=0.619, p=0.000), between LIS and LCS (r=0.560; p=0.000); and between IMTS and LCS (r=0.820; p=0.000). Learning institutions must adapt to the emerging Education 4.0 brought about by the new industrial era and the 21st-century society so that learners can thrive to the current and evolving challenges. A proposed training program is recommended for implementation to enhance the students’ 21st-century skills.